2015
DOI: 10.1002/pros.22976
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical and contradictory effects of imatinib in two cell line models of hormone-refractory prostate cancer

Abstract: DU145 and PC3 cells displayed a contradictory behavior in response to imatinib, which was underpinned by a distinct expression pattern (or activity) of target regulators of cell-cycle, apoptosis, and angiogenesis. The paradoxical effect of imatinib in PC3 cells may be related with the differential expression of c-KIT protein variants. Moreover, the present findings helped to understand the discrepancies in the efficacy of imatinib as therapeutic option in HRPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 85 publications
1
12
0
Order By: Relevance
“…ABL, the main target of imatinib and nilotinib, was found in PCa cell lines (CWR22Rv1, DU145, LNCaP, and PC‐3 cells), as were other targets, including c‐KIT and PDGFR . The anti‐tumor effects of these drugs on PCa cell lines have been investigated . Consistent with our data, imatinib shows antiproliferative effects on DU145, LNCaP, and PC‐3 cells .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…ABL, the main target of imatinib and nilotinib, was found in PCa cell lines (CWR22Rv1, DU145, LNCaP, and PC‐3 cells), as were other targets, including c‐KIT and PDGFR . The anti‐tumor effects of these drugs on PCa cell lines have been investigated . Consistent with our data, imatinib shows antiproliferative effects on DU145, LNCaP, and PC‐3 cells .…”
Section: Discussionsupporting
confidence: 87%
“…NRTKs such as ABL, SRC, and Janus kinase (JAK) have known roles in the biological processes of cell proliferation, migration, invasion, apoptosis, and angiogenesis in PCa . ABL, the main target of imatinib and nilotinib, was found in PCa cell lines (CWR22Rv1, DU145, LNCaP, and PC‐3 cells), as were other targets, including c‐KIT and PDGFR . The anti‐tumor effects of these drugs on PCa cell lines have been investigated .…”
Section: Discussionmentioning
confidence: 99%
“…8), which followed a previous study showing that RGN is overexpressed in radioresistant pancreatic cell lines established by fractionated irradiation [45]. Also, another study showed A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 25 accelerated healing of radiation-induced injury in mice liver concomitant with increased levels of RGN [72].…”
Section: Accepted Manuscriptmentioning
confidence: 79%
“…Caspase-3 activity assay was performed as previously described [25]. Briefly, 25 μg of total protein extracted from testicles were incubated with reaction buffer (25 mM HEPES, 0.1% CHAPS, 10% sucrose and 10 mM DTT, pH 7.5)…”
Section: Caspase-3 Activity Assaymentioning
confidence: 99%
“…To determine whether MLN4924 could enhance radiation efficacy, we performed radiosensitization experiments in two hormone-resistant prostate cancer cell lines, DU145 and PC3 [24, 25]. Firstly, we determined the sensitivity of the two prostate cancer cell lines to MLN4924 as a single agent.…”
Section: Resultsmentioning
confidence: 99%